Advancements in the integration of isothermal nucleic acid amplification methods for point-of-care testing in resource-limited settings - Noemi Bellassai; Roberta D'Agata; Giuseppe Spoto (Sensors and Actuators Reports)
Environmental conditions in low-resource areas exert significant pressure on populations, healthcare personnel, and the tools used for disease diagnosis. Fortunately, advancements in molecular assays now allow for rapid and efficient analysis, leading to effective clinical diagnostics and food safety interventions. Additionally, developing microfluidics and nanotechnologies has facilitated the miniaturization of integrated devices for point-of-care (POC) testing. These innovations have improved sensitivity while significantly reducing the time and cost associated with individual analyzes. This review focuses on the applications of molecular diagnostics for POC devices in low-resource settings, with a particular emphasis on isothermal nucleic acid amplification assays integrated into microfluidic platforms. It begins with an overview of the unmet needs for POC testing and its importance in resource-limited areas. Following this, isothermal amplification methods are described, highlighting their advantages and limitations when implemented in POC platforms, along with real-world applications in biological and food matrices in low- and middle-income countries. We then examine the unique features of POC systems, such as the use of low-cost materials for device fabrication, portability, and detection methods that provide rapid and reliable results near the site of patient care. This capability enables early-stage diagnosis and improved clinical management in low-resource environments.